Respuesta :

Answer:

  5y +6 +7y = 2 (6y + 3 )

Step-by-step explanation:

We can name the blanks 'a' and 'b'. Then we have ...

  5y +6 +7y = a(6y +b)

This will have infinitely many solutions when both sides simplify to the same expression.

  12y +6 = 6ay +ab

To have these expressions be the same, we must have ...

  12 = 6a . . . . same coefficient of y

  6 = ab . . . .  same constant

The first of these equations tells us ...

  a = 12/6 = 2

Then the second equation tells us ...

  b = 6/a = 6/2 = 3

The equation with the blanks filled in is ...

  5y +6 +7y = 2 (6y + 3 )